Characterization and reduction of line-to-line crosstalk on printed circuit boards - Welch, Joshua Adam (Kansas State University, 2018)
An important concern for high speed circuit designs is that of crosstalk and electromagnetic interference. In PCB board-level designs, crosstalk at microwave frequencies may result from imperfections in shielding of PCB interconnects or more generally transmission lines. Several studies have been done to characterize and improve the isolation between PCB transmission lines for both digital and RF circuits. For example, previous studies in the microwave region have examined the effect that line type, line length, and separation have on crosstalk and suggest that without full shielding, the upper limit of isolation is on the order of 60dB for traditional board-level lines [1]. In order to more fully characterize crosstalk and improve isolation above 60 dB, this thesis studies signal-to-ground-plane separation, considers advanced line types, and examines the effect of 3D shielding. Results are presented from 100MHz to 30GHz for the traditional transmission line structures of microstrip, CPW, differential pair and CPW differential pair. This study shows that with a halving of distance between signal and ground planes, isolation between transmission lines can be reduced by as much as 20dB, making this one of the best ways to improve performance. Advanced methods of shielding are then presented. Direct launch stripline and single-sided CPW improve upon existing crosstalk reduction techniques, while split shielding and ablation of dielectric PCB material are also proposed. The data and additional crosstalk reduction techniques discussed in this thesis serve two purposes. One: with a more complete understanding of the effects that transmission line types and parameters have on crosstalk, engineers can quickly identify potential crosstalk issues and resolve them before manufacturing. Second, this thesis presents the engineer with four new additional techniques that may become available in advanced manufacturing environments. Such techniques can further reduce crosstalk and may allow for isolation values to approach 100 dB at the PC board level.
Keywords: Crosstalk; FEXT; PCB; Single-Sided CPW; CPW; Microstrip